The Combustion Characteristics of Calophyllum inophyllum Fuel in the Presence of Magnetic Field - Sugara, Imam Rudi; Ilminnafik, Nasrul; Junus, Salahuddin; Kustanto, Muh Nurkoyim; Hermawan, Yuni (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
The study objective is to investigate the combustion characteristics of Callophyllum inophyllum fuel in presence of a magnetic fields. To conduct the experiment, a bunsen burner was utilized, with fuel and air being dispensed via a syringe pump and compressor, both regulated by a flowmeter. The fuel and air pipes were heated to 532.15 (K) to facilitate fuel evaporation. The equivalent ratio of 0.5, 1, and 1.5 was adjusted to control air discharge and fuel. An 11,000 gausses artificial magnet was used, with N-S, N-S, N-N, and S-S being the various magnetic pole configurations. The study found that the magnetic field can enhance combustion quality by affecting the molecules involved in the combustion process. The magnetic field's force also intensifies the movement of O2, making it more energetic. As O2 travels from the North Pole to the South Pole through the combustion reaction zone, it quickens the oxidation-reduction process and curtails diffusion combustion. The red color's intensity diminishes with the magnetic field's effect, indicating this phenomenon. When a magnetic field is applied, the polarity of C.inophyllum biodiesel fuel becomes highly favorable. The triglyceride carbon chain bonds become unstable, and the van der Walls dispersion forces are weakened, which facilitates easier O2 binding to the fuel, resulting in more efficient combustion. An increase in the laminar burning velocity value can be noticed when exposed to a magnetic field.